Integrasi Ekonomi dan Spiritual Pemikiran Al-Syaibani dalam Hukum Ekonomi Syariah - Akbar Muhamad Ashoni; Mia Amanatul Fitriyah (STAI Al-Mas'udiyah, 2025)
This paper explores the economic thought and legal framework of Islamic economics during the era of Al-Syaibani, a significant figure in the history of Islamic economic thought known for his contributions to understanding the concepts of work and production within an Islamic context. Al-Syaibani emphasizes the role of humans as stewards (khalifah) on earth, responsible for utilizing resources in a manner that promotes the welfare of all beings. In his view, production activities are not merely about seeking profit but are also part of the obligation to create sustainable prosperity for humanity. His renowned work,